Mothers overcoming remorse to care for self and baby: An emerging concept - Heather Lynn Coddington (International Journal of Nursing Sciences, 2022)
Objectives: Mothers with substance use disorder (SUD) experience a range of emotions such as feeling ostracized, diminished, and distressed while watching their baby experience withdrawal from substances. Being fully present in the now moment is to trust self to do what is best by moving beyond perceived boundaries to care for self and baby. The process of concept building arose from nursing practice encounters in a special care nursery (SCN) for babies who experienced withdrawal from substances. Method: Liehr and Smith’s 10-phase concept building approach was used to guide the development of this concept. Concept building began with a practice story. The emerging concept was named, core qualities identified, and supported through a literature review. The middle range theory of uncertainty in illness was chosen to serve as theoretical support for the concept. A model was created to provide clarity on the relationships within the concept. Result: A mini-saga was gathered from a mother in the SCN whose newborn had experienced withdrawal from substances. The minisaga follows: Due to the baby’s discomfort and judging eyes of the staff, she was unable to mother her baby. As the baby recovered, she asked for help, comforted her baby, and gained confidence to move beyond perceived boundaries to become the mother she envisioned. Overcoming perceived boundaries to attend to self and baby is trusting oneself to do what is best in spite of feeling ostracized, diminished, and distressed while watching baby withdraw from substances. Conclusion: This concept provides the perspective of mothers with SUD through intermodernism from experiences in nursing practice. The Uncertainty in Illness theory further allows practitioners to gain an understanding of the role uncertainty plays in this unique situation.